Novel functional nano-coatings on glass by spray deposition - Wang, W (2010)
Nanocomposite thin films with gold nanoparticles embedded in a host metal oxide prepared by spray pyrolysis deposition have been investigated. A single-step process has been developed using a one-pot solution containing precursors for both gold nanoparticles and host metal oxides. The films obtained display combined features of colouration, electrical conductivity and solar control. In this study two precursors for gold nanoparticles were used: preformed gold colloids and HAuCl4. Three metal oxide host materials, TiO2, SnO2 and ZnO, were investigated. These films were deposited at a substrate temperature of 200-600 °C. Powder X-ray diffraction analysis reveals the presence of metallic gold. SEM inspection typically showed particulate gold of 5-20 nm in diameter, distributed at the surface or within the host matrix. Optical spectroscopy showed an intense absorption in the visible region due to the characteristic surface plasmon resonance (SPR) effects of gold nanoparticles. The wavelength of the SPR peaks varies depending on the refractive index of surrounding host material which is significantly influenced by the substrate deposition temperature. On the other hand, SnO2 and ZnO, together with the introduction of dopants, were further investigated as suitable materials for transparent conducting oxides (TCO). SnO2:F films were found to attain very low electrical resistivity, while ZnO films exhibit higher transparency in the visible. A double layered structure with a TCO layer of SnO2:F on top of a layer embedded with gold nanoparticles has been employed to achieve the combined functionalities of conductivity and colouration. The electrical conductivity is significantly enhanced compared to a nanocomposite single layer film due to the introduction of the TCO top layer. In this thesis, spray pyrolysis deposition has demonstrated a simple and rapid approach to the production of a variety of thin films. It can be immediately integrated with current industrial coating equipment and scaled up for large-scale production process.